FACTORS WHICH AFFECTS INCOME ORIGINAL REGIONAL (PAD) TOURISM IN HULU SUNGAI UTARA REGENCY - Azmy Pratama; R Rizali (Ecoplan, 2019)
Hulu Sungai Utara Regency is one of the districts in South Kalimantan that has potential in the tourism sector because it has a large number of tourism objects.This potential has not been able to increase the regional income of the tourism sector in a significant amount.This study aims to determine the effect of population, hotel occupancy rates, and the number of tourists on regional income in the tourism sector in Hulu Sungai Utara Regency. Types and sources of data using a quantitative approach in analyzing the effect of Total Population (X1), Hotel Occupancy Rate (X2) and Number of Tourists (X3) on Regional Original Revenues of the Hulu Sungai Utara Tourism Sector in 2008-2018 were carried out using the Ordinary Least Squares method (OLS).Analysis of this model uses Eviews 9 computer program tools . Based on multiple linear regression analysis, the equation model is obtained: PAD = -1,6300 + 7465,497 P + 38877.68 THH + 414,9256 JW + e.The equation is tested with the meaning of the probability of the t test, with a population variable tcount of 0.0471, the Hotel Occupancy Rate variable with tcount of 0.0022 and for the variable number of tourists is 0.6629, the probability of the two variables is smaller than the real level used ie 0.05 while one variable is greater than the real level used in 0.05.While the F test is 0.4730> Ftable 0.05 whose decision is non-autocorrelation. The conclusions of this study indicate that the population and occupancy rates of the hotel influence the regional income of the tourism sector of Hulu Sungai Utara Regency, while the number of tourists does not affect the regional income of the tourism sector of the Hulu Sungai Utara Regency.The low number of tourists visiting Hulu Sungai Utara Regency is due to the lack of optimal role of the government in managing existing tourism. Related to this research, it is recommended that the Hulu Sungai Utara District Government increase tourism promotion and make improvements to various tourism facilities and build souvenir shops for increase regional income in the tourism sector of Hulu Sungai Utara Regency. Keywords: Population, Hotel Occupancy Rate, Number of Travelers, Regional Revenue of the Tourism Sector